A CRITICAL ANALYSIS OF GENDER DIFFERENCES IN SUICIDE IDEATION AND ATTEMPTS AMONG SECONDARY STUDENTS IN MURANGA COUNTY, KENYA (Isagoge - Journal of Humanities and Social Sciences, 2021)
The contemporary society is characterized by several problems among students in the secondary schools. Some may be psychosocial leading to suicide ideation and attempts. This study sought to assess the psychosocial factors in public secondary schools in Murang’a County. The objectives of the study were to explore the gender differences on suicide ideation and attempts among learners in public secondary school students in Murang’a County, Kenya. This study was guided by the psychosocial theory by Eric Erickson, Interpersonal theory by Thomas Jioner and Psychological theory by Edwin Scheidman. This was a mixed methodology study, whose design was survey and ex- posto facto for quantitative research while phenomenology was for qualitative research for the purpose of data triangulation.  The target population comprised of the 5940 students, 116 Guidance and Counseling teachers, 289 class teachers and 8 sub county educational officers, parents and suicide attempters. Overall, the sampled respondents were 642 covering all the categories of the study comprising 560 students using cluster sampling, suicide attempters and parents using snowballing, 56 class teachers, 8 sub county educational officers and 28 Guidance and Counseling teachers were sampled using purposive sampling. The data collection instruments comprised of questionnaires for the students, interview guide for Guidance and Counseling teachers, Sub County Educational Officers, interview guide for parents and suicide attempters and focused group discussions for the teachers. The collected data was analyzed using thematic analysis for qualitative data while quantitative data was analyzed using both descriptive and inferential statistics like frequency tables and the regression model. The findings established and concluded that personality traits, family history, school set-up and society setting had significant contribution to the frequency of suicide ideation and attempts in Murang’a County, Kenya. The study established that while girls attempt suicide more, it is the boys who die more since they use lethal means. The study recommended the empowerment of the students both boys and girls on positive self-esteem and confidence by the teachers, the use of various psychological therapies to deal with personality disorders by the guidance and counseling teachers.
Keywords: Gender differences; Suicide; Suicide ideation; Suicide attempts